Verkkosovellusten haavoittuvuuksien tunnistaminen käytön aikana - Ruohoniemi, Miikka (2025)
The identification of vulnerabilities is increasingly being automated as much as possible. While this can help detect vulnerabilities more comprehensively, it may also give users a false sense of security and expose them to cyber threats. This thesis explores whether users can identify vulnerabilities in web applications without the use of automated tools. The study first examined how vulnerabilities are typically assessed, followed by an analysis of the most common web application vulnerabilities based on the OWASP Top 10 categories and the MITRE Top 25 Most Dangerous Software Weaknesses list.